Integrating Islamic Values into Science Education: A Narrative Literature Review on Student Competencies and Pedagogical Implications - Ibnul Mubarok; Fenia Revalina; Zaitullah; Ririn Dwi Ariyanti; Putri Farhanah Sudirman; Wilda Rusdiana (Journal of Progressive Science Education, 2026)
Science education in Islamic educational institutions is expected to foster scientific competencies while strengthening students’ faith, character, and spiritual identity. However, evidence regarding the impact of integrating Islamic values into science education remains scattered across various competency domains. This study aims to synthesize the reported impacts of integrating Islamic values on student competencies, identify factors influencing its implementation, and interpret these findings through the theory of worldview and the tauhid paradigm. A narrative literature review was conducted by analyzing relevant publications obtained from Scopus, ERIC, SINTA, ProQuest, Google Scholar, and supporting references using thematic and critical interpretive synthesis. The review revealed four consistent patterns: improved cognitive and academic achievement, the development of higher-order thinking skills, the formation of moral and spiritual character, and the influence of teacher competence, institutional support, curriculum flexibility, and epistemological coherence on its implementation. Overall, the integration of Islamic values into science education provides a holistic framework for developing students’ cognitive, intellectual, and moral competencies, although stronger longitudinal and cross-cultural evidence is still needed to establish its long-term effectiveness and broader application.